2016
DOI: 10.1242/jcs.188219
|View full text |Cite
|
Sign up to set email alerts
|

VEGF induces signalling and angiogenesis by directing VEGFR2 internalisation through macropinocytosis

Abstract: Endocytosis plays a crucial role in receptor signalling. VEGFR2 (also known as KDR) and its ligand VEGFA are fundamental in neovascularisation. However, our understanding of the role of endocytosis in VEGFR2 signalling remains limited. Despite the existence of diverse internalisation routes, the only known endocytic pathway for VEGFR2 is the clathrin-mediated pathway. Here, we show that this pathway is the predominant internalisation route for VEGFR2 only in the absence of ligand. Intriguingly, VEGFA induces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 66 publications
16
58
0
Order By: Relevance
“…Given that both tools (siRNA of CHC and dynasore) inhibited effectively the uptake of transferrin (a typical cargo-marker of CME) (Fig. 1a,b), it is concluded that partial inhibition of VEGFR2 internalisation (by the above tools) is not due to insufficient blockage of CME, but rather due to a partial contribution of this pathway in VEGFR2 internalisation, which is in line with previous reports1819242628. Furthermore, since CHC knockdown and dynasore inhibited internalisation of VEGFR2 to the same extent (up to 20–30%), we conclude that these tools are consistent in blocking CME of VEGFR2.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Given that both tools (siRNA of CHC and dynasore) inhibited effectively the uptake of transferrin (a typical cargo-marker of CME) (Fig. 1a,b), it is concluded that partial inhibition of VEGFR2 internalisation (by the above tools) is not due to insufficient blockage of CME, but rather due to a partial contribution of this pathway in VEGFR2 internalisation, which is in line with previous reports1819242628. Furthermore, since CHC knockdown and dynasore inhibited internalisation of VEGFR2 to the same extent (up to 20–30%), we conclude that these tools are consistent in blocking CME of VEGFR2.…”
Section: Resultssupporting
confidence: 90%
“…To assess the amount of internalised VEGFR2, we followed an anti-VEGFR2 antibody uptake protocol, followed by analysis by confocal microscopy1821232637, in primary human umbilical vein endothelial cells (HUVECs). This method reveals the molecules of newly internalised VEGFR2, while it excludes the non-internalised and intracellular pools of the receptor.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations